Crystallization of poly(butylene 2, 6‐naphthalate) containing diethylene 2, 6‐naphthalate constitutional defects. Issue 4 (20th December 2018) - Ding, Qian; Soccio, Michelina; Lotti, Nadia; Mahmood, Nasir; Cavallo, Dario; Androsch, René
Abstract: The effect of presence of up to 30 mol% diethylene 2, 6‐naphthalate (DEN) constitutional defects on the crystallization kinetics and morphology of poly(butylene 2, 6‐naphthalate) (PBN) was investigated by differential scanning calorimetry, fast scanning chip calorimetry, polarized‐light optical microscopy, and wide‐angle X‐ray scattering (WAXS). The results indicate that the crystallization behavior of butylene/DEN random copolymers [P(B x DE y N)] is analogous to the PBN homopolymer: at low supercooling direct crystallization from the melt occurs, while at lower crystallization temperature/higher cooling rates, the formation of a liquid crystalline phase precedes the development of the ultimately stable crystal, confirming the validity of Ostwald's rule of stages also for random copolymers. However, the incorporation of DEN counits into the polymer chains retards both crystal and liquid‐crystal formation proportionally to the DEN content. WAXS analysis suggests the exclusion of DEN counits from PBN crystals. Thus, the lower crystallization rate in the copolymers can be associated, with the filtering of crystallizable chain segments at the crystal growth front. Abstract : Investigation of crystallization kinetics and morphology has great significance to improve the thermal and mechanical properties of random copolymers based on poly(butylene 2, 6‐naphthalate). The presence of diethylene 2, 6‐naphthalate (DEN) counits hinders the melt crystallization and the transformation of the melt into crystals via intermediate formation of liquid crystals (LC), especially at high DEN content. The general cooling‐rate‐dependent path of solidification preserves the melt even in copolymers containing 30 mol% DEN counits, although the critical cooling rates for observing the various transitions (melt‐crystal, melt‐LC, and LC‐crystal) vary largely.